Synthesis and biological evaluation of some New fused heterocyclic azine derivatives - Mahmoud Aly Mourad Metwally; Magda Ahmed Abdallah; Sobhy Mohamed Gomaa (Cairo : Mahmoud Aly Mourad Metwally, 2016)
A new series of pyrido[2',3':4,5] pyrimido [2,1-b][1,3,5] thiadiazinones were prepared by aminomethylation of pyridopyrimidinethione with a variety of primary aromatic amines and formaldehyde solution (37%) through mannich reaction. Also, another series of pyrido[2', 3:4,5] pyrimido [2,1-b] [1,3] thiazinones were synthesized by michael addition reaction of pyridopyrimidinethione to the activated double bond of a number of arylidene malononitrile and ethyl 3-aryl-2-cyanopropenoate. The mechanism of formation of the synthesized compounds was discussed and the assigned structure was established via microanalysis and spectral data (IR, 1HNMR and Mass). In addition, the antitumor activities of the synthesized compounds were investigated and the results revealed that these compounds exhibited promising activities against HepG-2 and MCF-7 cancer cell lines. In the second project: 2-Hydrazinyl-5,7-di-p-tolylpyrido [2,3-d] pyrimidin-4 (3H)-one was prepared and condensed with different aldehydes to give the corresponding hydrazone derivatives. Oxidative cyclization of the latter compounds gave the corresponding pyrido [2,3- d] [1,2,4] triazolo [4,3-a] pyrimidin-5 (1H)-one derivatives. Furthermore, the hydrazinyl compound reacted with benzoyl chloride, triethyl orthoformate, acetyl chloride, ethyl chloroformate and carbon disulphide in alcoholic KOH solution to afford the corresponding pyrido [2,3- d][1,2,4] triazolo [4,3-a]pyrimidinones. The reaction of 2-thioxo-5,7-di-p-tolyl-2,3- dihydropyrido [2,3-d]pyrimidin-4(1H)-one or its 2-methylthio derivative with hydrazonoyl halides in dioxane under reflux, in the presence of triethylamine, yielded the corresponding pyrido 2,3-d 1,2,4triazolo 4,3-a pyrimidinones
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Organic Chemistry
Issued also as CD
Keywords: Azine derivatives; Biological evaluation; New fused heterocyclic